Transient Receptor Potential Canonical Channels 4 and 5 Mediate Escherichia coli-Derived Thioredoxin Effects in Lipopolysaccharide-Injected Mice. (10th June 2018) - Pereira, Domingos M. S.; Mendes, Saulo J. F.; Alawi, Khadija; Thakore, Pratish; Aubdool, Aisah; Sousa, Nágila C. F.; da Silva, João F. R.; Castro, José A.; P. Pereira, Ione C.; Silva, Luís C. N.; Grisotto, Marcos A. G.; Monteiro-Neto, Valério; et al.
Abstract : Thioredoxin plays an essential role in bacterial antioxidant machinery and virulence; however, its regulatory actions in the host are less well understood. Reduced human Trx activates transient receptor potential canonical 5 (TRPC5) in inflammation, but there is no evidence of whether these receptors mediate bacterial thioredoxin effects in the host. Importantly, TRPC5 can form functional complexes with other subunits such as TRPC4. Herein, E. coli -derived thioredoxin induced mortality in lipopolysaccharide- (LPS-) injected mice, accompanied by reduction of leukocyte accumulation, regulation of cytokine release into the peritoneum, and impairment of peritoneal macrophage-mediated phagocytosis. Dual TRPC4/TRPC5 blockade by ML204 increased mortality and hypothermia in thioredoxin-treated LPS mice but preserved macrophage's ability to phagocytose. TRPC5 deletion did not alter body temperature but promoted additional accumulation of peritoneal leukocytes and inflammatory mediator release in thioredoxin-administered LPS mice. Thioredoxin diminished macrophage-mediated phagocytosis in wild-type but not TRPC5 knockout animals. TRPC5 ablation did not affect LPS-induced responses. However, ML204 caused mortality associated with exacerbated hypothermia and decreased peritoneal leukocyte numbers and cytokines in LPS-injected mice. These results suggest that bacterial thioredoxin effects under LPS stimuli are mediated by TRPC4 and TRPC5, shedding light on the additional mechanisms of bacterial virulence and on the pathophysiological roles of these receptors.